Some issues of prosecutor’s participation in proceedings on administrative offences: based on the European Court of Human Rights case law - S. O. Shatrava; О. V. Dzhafarova; О. V. Pohorilets (Bulletin of Kharkiv National University of Internal Affairs)
The scientific work focuses on reviewing the works of scholars who have studied various aspects of the implementation of judgments of the European Court of Human Rights. However, the issues of human rights protection and observance of the principle of competition during the consideration of an administrative offence case remain unaddressed.